Homalothecium meridionale (M.Fleisch. & Warnst.) Hedenäs: a distinct species from H. sericeum (Hedw.) Schimp. (Brachytheciaceae, Bryopsida) in the Iberian Peninsula. (2nd January 2017) - Sérgio, C.; Garcia, C. A.; Sim-Sim, M.; Vieira, C.; Hespanhol, H.; Stow, S.; Guerra, J.
Abstract : Previous molecular studies have done much to shed some light on the taxonomy and phytogeographic position of Homalothecium sericeum and H. meridionale and the present study clarifies the taxonomy and distribution of the two species across Iberia. By conducting a revision of Homalothecium specimens available in Spanish and Portuguese herbaria, we concluded that sporophytic differences are the most appropriate characters for the delimitation of each species. Scanning electron microscope examination of the peristomes of the two taxa helped distinguish between them. We also noted that H. meridionale is a frequently distributed taxon throughout the Iberian territory, but occurs mostly in Portuguese areas with a Mediterranean influence, becoming less frequent in the Atlantic as well as in continental parts of the Peninsula. As a result of this study, based on numerous new localities in Portugal and Spain, we provide an updated map of the distribution of H. meridionale, and an account of its ecology and habitat affinities.